Computational fluid dynamics investigation on effects of uvulopalatopharyngoplasty on upper airway stability - Shang, Yan; Hu, Bin; Yin, Guoping; Fu, Song; Ye, Jingying (AIP advances, 2021)
Uvulopalatopharyngoplasty (UPPP) is a widely accepted surgery to treat patients with obstructive sleep apnea. However, the outcomes of surgery are variable and not satisfactory in many cases. To explore the key factors that influence outcomes of surgery from perspectives of upper airway stability using computational fluid dynamics methods, three-dimensional (3D) upper airway models were reconstructed, and a series of steady-state and unsteady-state simulations were performed based on computerized tomography (CT) scans of five normal subjects and preoperative and postoperative CT scans of ten obstructive sleep apnea (OSA) patients. Aerodynamics in normal subjects, preoperative OSA patients, and postoperative OSA patients was compared, and the outcomes of UPPP were analyzed from perspectives of upper airway resistance and the wall pressure–inspiratory pressure ratio. The negative pressure on the collapsible part of the upper airway was a major contributor to the obstruction. Surgery mitigated the negative pressure by reducing the upper airway resistance as well as the wall pressure–inspiratory pressure ratio. The effect of UPPP was associated with the change in resistance and the wall pressure–inspiratory pressure ratio.